CORPORATE SOCIAL RESPONSIBILITY RESOR NIHIWATU SEBAGAI BENTUK PENGEMBANGAN EKOWISATA DI KABUPATEN SUMBA BARAT - Yohanis Umbu Roru; I Nyoman Darma Putra; I Wayan Suardana (JURNAL MASTER PARIWISATA, 2018)
The research aimed to investigate (1) CSR program conducted at Nihiwatu Resort, (2) factors that drive the implementation of CSR, and (3) implementation impact of CSR in ecotourism development in West Sumba Region. Data analysis was done descriptively qualitativeby applying stakeholder theory, theory of legitimacy, theory of corporate citizenship and impact theory. The results showed that CSR activities run by Nihiwatu Resort were not only incidental CSR but a sustainable one.The driving factors of CSR were as a form of moral obligation, to improve the company image, and to gain pro t. The social impacts were gaining government support and publicacceptance, proximity to health services; and easy access to clean water. Economic impacts include creating employment opportunities and improving economic structures. While the ecological impacts of the CSR programs are the the minimization of energy consumption generated through the use of vernacular concepts in all existing properties.